1997
DOI: 10.1128/iai.65.7.2564-2569.1997
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary response to Histoplasma capsulatum in gamma interferon knockout mice

Abstract: We examined the immunobiological responses to Histoplasma capsulatum in lungs of gamma interferon (IFN-␥) knockout mice (GKO mice). Naive GKO mice succumbed by day 9 to intranasal challenge with 2.5 ؋ 10 6 yeasts, whereas all wild-type (WT) mice survived for 45 days. Compared to lungs of WT mice, the lungs of acutely infected GKO mice exhibited dramatically elevated numbers of CFU in lungs and significantly higher levels of tumor necrosis factor alpha (TNF-␣) and granulocyte-macrophage colony-stimulating facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
4

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 23 publications
0
29
0
4
Order By: Relevance
“…Activation of adaptive immunity generally develops after 7 days of nonlethal pulmonary infection with H. capsulatum [31,32]. These studies were also limited to 7 days, as neutralization of TNF-␣ and IFN-␥ leads to the demise of animals between Days 8 and 14 of infection [7,14]; thus, comparisons between cytokine-deficient and cytokine-sufficient mice could only take place during the first week to avoid analysis of moribund animals.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of adaptive immunity generally develops after 7 days of nonlethal pulmonary infection with H. capsulatum [31,32]. These studies were also limited to 7 days, as neutralization of TNF-␣ and IFN-␥ leads to the demise of animals between Days 8 and 14 of infection [7,14]; thus, comparisons between cytokine-deficient and cytokine-sufficient mice could only take place during the first week to avoid analysis of moribund animals.…”
Section: Discussionmentioning
confidence: 99%
“…Innate cytokine production is also important in early control of infection, as the neutralization of granulocyte–macrophage colony‐stimulating factor (GM‐CSF) results in an order of magnitude higher fungal burden in the lungs by 1 week post infection . Ablation of GM‐CSF also impairs the early production of tumour necrosis factor‐ α (TNF‐ α ) and IFN‐ γ , two cytokines that are likewise critical for the control of H. capsulatum infection . CCR2‐dependent inflammatory cell recruitment is also crucial for early control of infection, as CCR2 −/− mice show a significant increase in lung fungal burden by 7 days post infection, which involves tilting T helper cell immunity away from Th1 responses.…”
Section: Type 1 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…Numerous studies have demonstrated that Th1 responses are protective against H. capsulatum infection . Mice deficient in IFN‐ γ signalling are exquisitely susceptible to experimental H. capsulatum infection, dying in little more than a week after experimental infection . In immunocompetent mice, the kinetics of IFN‐ γ production from CD4 T cells correlates well with the clearance of the fungus from the lungs .…”
Section: Type 1 Responses To Pulmonary Mycosesmentioning
confidence: 99%
“…The mechanism that underlies this ability is unknown, but transcriptional analysis of RNS‐treated yeasts identified 59 genes that are up‐regulated in response to nitrosative stress . Cytokine activation of phagocytes stimulates RNS production, and reduced pro‐inflammatory cytokine levels are correlated with increased susceptibility of mice to H. capsulatum infection . These data suggest that RNS control H. capsulatum yeast, but that RNS‐based control functions during the adaptive immunity stage of infection rather than the initial infection of phagocytes.…”
Section: Intracellular Challengesmentioning
confidence: 99%